2021
DOI: 10.1177/14644193211065916
|View full text |Cite
|
Sign up to set email alerts
|

A vibration model of a rotor system with the sinusoidal waviness by using the non-Hertzian solution

Abstract: The nonlinear contact forces and deformations between the balls and raceways can cause very complex vibration behaviours of rotor systems with the waviness in the support bearings. However, almost all previous works that used sinusoidal waviness took the Hertzian solution as the calculation method, which is not an accurate method based on Johnson’s formulation since the changes in the curvature at the sinusoidal contact surfaces. To overcome this issue, a new dynamic model of a rigid rotor system with the wavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition to the effect of the clearance, Liu et al 25 presented the bearing lubrication coupled model including the dynamics model and lubrication model by considering the effect of the cage clearance and the lubrication. Furthermore, researchers have concluded that the rolling bearing components' flexible deformation, 26,27 manufacturing errors, 28,29 local defect 30 can greatly affect the vibration characteristics of the ball bearing-shaft system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect of the clearance, Liu et al 25 presented the bearing lubrication coupled model including the dynamics model and lubrication model by considering the effect of the cage clearance and the lubrication. Furthermore, researchers have concluded that the rolling bearing components' flexible deformation, 26,27 manufacturing errors, 28,29 local defect 30 can greatly affect the vibration characteristics of the ball bearing-shaft system.…”
Section: Introductionmentioning
confidence: 99%
“…Clearance is one of the important influence factors of bearing nonlinear characteristics, which must be produced by the manufacturing processing. 3 Therefore, it is important to study the influence of a turbine supporting bearing clearance on the vibrations of the TRS, which could help in controlling the vibrations of TRSs.…”
Section: Introductionmentioning
confidence: 99%